Altered melatonin production in TGR(mREN2)27 rats: on the regulation by adrenergic agonists, antagonists and angiotensin II in cultured pinealocytes - Enzminger, Helene; Witte, Klaus; Lemmer, Björn (Journal of pineal research, 2001)
Transgenic TGR(mREN2)27 rats (TGR), carrying an additional mouse renin gene, are characterized by severe hypertension, an inverse circadian blood pressure profile, a blunted response to photic entrainment signals, and an increased nocturnal production of the pineal hormone melatonin. In order to evaluate the contribution of the over-expressed renin-angiotensin system to the function of the pineal gland in TGR, we studied the adrenergic and angiotensin II (Ang II)-mediated regulation of melatonin synthesis using dispersed pinealocytes from TGR and from Sprague-Dawley control rats (SDR). Isoproterenol was more effective in stimulating melatonin release in pinealocytes from TGR than from SDR, whereas the maximum effect of norepinephrine (NE) stimulation did not differ between the strains. Prazosin reduced the NE-mediated melatonin release only in SDR but not in TGR pinealocytes. Competition experiments with (±)-, (+)-, (−)-propranolol and (±)-atenolol revealed one homogenous population of β1-adrenoceptors. Ang II had no significant effect on basal or isoproterenol-induced melatonin release in either strain. In conclusion, TGR pinealocytes were more sensitive to β-adrenergic stimulation than SDR pinealocytes, but lacked the α1-adrenergic potentiation of β-adrenergic induced melatonin release. The renin-angiotensin system was not directly involved in the regulation of melatonin synthesis by rat pinealocytes in vitro.